The Effectiveness of Village Governments in Improving the Quality of Public Services - Nurul Alfenia; Rahmat Hidayat; Rudyk Nababan (Jurnal Ilmiah Wahana Pendidikan, 2022)
Optimal public service in government administration is a concrete manifestation of creating good governance.. Based on Law Number 6 of 2014 concerning Villages, that forming a village government that is professional, efficient, and effective, open and accountable is inseparable from optimal public services in the implementation of village governance. This study aims to describe the effectiveness of the village government in improving the quality of public services to the community in Pasirtalaga Village. This research was studied using descriptive research and qualitative methods with data collection techniques using the interview method, and obtaining data by direct observation of the symptoms studied. The research results reveal that the effectiveness of the village government in improving the quality of public services in Pasirtalaga Village is quite effective, seen from 3 (three) indicators of measuring the effectiveness of Duncan quoted by Richard M. Steers (1985: 53), namely goal achievement, integration, and adaptation. However, there are still several obstacles, including the socialization process that has not been conveyed properly, the village government has not been able to utilize technology, and the facilities and infrastructure are still inadequate